Examination of body checking, body image dissatisfaction, and negative affect using Ecological momentary assessment. (August 2016) - Stefano, Emily C.; Hudson, Danae L.; Whisenhunt, Brooke L.; Buchanan, Erin M.; Latner, Janet D.
Abstract: Research has shown that non-clinical women, particularly those with high body concern, engage in frequent body checking behaviors. The purpose of this study was to use ecological momentary assessment (EMA) to examine the frequency and correlates of body checking behavior, including its association with body image dissatisfaction and negative affect, in non-clinical women with high body concern. Undergraduate female participants with high body concern ( n = 22) were assessed five times per day for five days via text messages sent to their smart phones. During each assessment, participants reported the number of times they engaged in eight different body checking behaviors and their current level of negative affect and body dissatisfaction. After aggregation, a total of 3064 body checking behaviors were reported by the sample during the five-day period. All participants reported engaging in body checking at least once per day, with a mean of 27.85 checking behaviors per day. Hierarchical Linear Modeling revealed that body checking significantly predicted both body dissatisfaction and negative affect. These results provide preliminary support for the cognitive behavioral theory of eating disorders, suggesting that as women engage in more frequent body checking behaviors, they also experience higher levels of body dissatisfaction and negative affect. Highlights: Non-clinical women with high body concern frequently engage in body checking. Increased body checking predicted greater levels of body dissatisfaction and negative affect. Results suggest the cognitive behavioral theory of eating disorders may generalize to non-clinical women.